Review of endangered cattle breeds of Africa - Adeniji, K.O. (1983)
The indigenous breeds of cattle endangered in Africa are identified. Topical dicussions on main reasons for being endangered, their geographical distribution and numbers, their major contribution to economy and the specific traits justifying conservation programmes for the breeds included.